Association between immigrant status and advanced cancer patients' location and quality of death. Issue 18 (8th July 2022) - Tergas, Ana I.; Prigerson, Holly G.; Shen, Megan J.; Dinicu, Andreea I.; Neugut, Alfred I.; Wright, Jason D.; Hershman, Dawn L.; Maciejewski, Paul K.
Abstract : Background: Cancer patients often prefer to die at home, a location associated with better quality of death (QoD). Several studies demonstrate disparities in end‐of‐life care among immigrant populations in the United States. This study aimed to evaluate how immigrant status affects location and quality of death among patients with advanced cancer in the United States. Methods: Data were derived from Coping with Cancer, a federally funded multi‐site prospective study of advanced cancer patients and caregivers. The sample of patients who died during the study period was weighted ( N w = 308) to reduce statistically significant differences between immigrant ( N w = 49) and nonimmigrant ( N w = 259) study participants. Primary outcomes were location of death, death at preferred location, and poor QoD. Results: Analyses adjusted for covariates indicated that patients who were immigrants were more likely to die in a hospital than home (adjusted odds ratio [AOR], 3.33; 95% confidence interval [CI], 1.65–6.71) and less likely to die where they preferred (AOR, 0.42; 95% CI, 0.20–0.90). Furthermore, immigrants were more likely to have poor QoD (AOR, 5.47; 95% CI, 2.70–11.08). Conclusions: Immigrants, as compared to nonimmigrants, are more likely to die in hospital settings, less likely to die at their preferred location, and more likely to have poor QoD. Lay summary: Cancer patients typically prefer to die in their own homes, which is associated with improved quality of death. However, disparities in end‐of‐life care among immigrant populations in the United States remain significant. Our study found that immigrants are less likely to die in their preferred locations and more likely to die in hospital settings, resulting in poorer quality of death. Abstract : Disparities in end‐of‐life care and quality of death are prevalent among immigrants. The findings of this study illustrate that immigrants in the United States are more likely to die in hospital settings and less likely to die at their preferred location.